PREVALENCE OF OBESITY AND ITS ASSOCIATED RISK FACTORS AMONG POST- BASIC RENAL CARE NURSING STUDENTS - Aung Myo Oo; Al-abed Ali A. Al-abed; Ohn MarLwin; Sowmya Sham Kanneppady; Sham Kishor Kanneppady (Malaysian Journal of Public Health Medicine, 2019)
Obesity is one of the most common, yet among the most neglected, public health problems around the world and it is strongly associated with various non-communicable diseases such as hypertension, diabetes mellitus and coronary artery diseases. Health care personal especially nurses play an important role in educating public to have healthy lifestyle. However, there is an alarming rate of increase in number of obesity among nursing students as well as staff nurses. Therefore, the aim of this study was to determine the anthropometric measurements and its associated risks among post-basic renal care nursing students. Total of 142 post-basic renal care nursing students of five intakes were included in this cross-sectional study. The result of the study showed that 52% of participants were either overweight or obese although most of them were below 40 years of age. Majority of overweight or obese students were Malays and 78% of them being female. We also observed an association of systolic blood pressure (SBP), diastolic blood pressure (DBP) and waist circumference (WC)with increasing body mass index (BMI) (P= 0.001, P= 0.001 and P<0.001) which were statistically significant. Wald criterion estimated that WC and DBP were the most important predictors of BMI in present study. Our study concluded that obesity is prevalent among post-basic renal care nursing students. Urgent and appropriate action should be taken to deter the growing problem of obesity among nursing students and to avoid its subsequent complications in Malaysia.